Rapid Somatic Embryogenesis of Citrus reticulata Blanco cv. Madu in an Air-Lift Bioreactor Culture - Agisimanto, Dita; M. N., Normah; Ibrahim, Rusli (AGRIVITA, Journal of Agricultural Science, 2019)
Embryogenic cell (EC) growth and proliferation as well as somatic embryo induction were examined in a bioreactor culture using Murashige and Skoog basal medium particularly for the influence of 6-benzyladenine (BA) concentration, initial cell density and aeration rate. Embryogenic callus was induced from seeds of Citrus reticulata Blanco cv. Madu. The cell suspension in a 3-L bioreactor exhibited maximum cell growth following the addition of 1.5 mg/l of BA. The fresh weight (FW) of the cells after 28 days of growth was found to increase from an initial of 5.5 g cell culture to 57.3 g, a 10.4-fold increase and the maximum growth rate (GR) of the cells (0.33 g/day) was attained by the 7th day of culture. In the cell density experiment, ECs at a concentration of 5.5 g/l constituted the most effective inoculum, reaching the highest GR of ECs (0.52 g/day), again by the 7th day of culture. In the aeration experiment, the highest EC GR of 2.6 g/daywas obtained at the maximum aeration rate of 1.5 vvm (air volume medium/ volume/min). After 28 days of somatic embryogenesis, 79% of ECs became somatic embryos, of which 29% were at cotyledonary stage.